Controllable synthesis of graphene using novel aromatic 1, 3, 5-triethynylbenzene molecules on Rh(111)1. Issue 93 (11th October 2015) - Qi, Yue; Zhou, Xiebo; Liu, Mengxi; Li, Qiucheng; Ma, Donglin; Zhang, Yanfeng; Liu, Zhongfan
<x xml:space="preserve">Abstract</x> 1, 3, 5-Triethynylbenzene is selected as carbon precursor for graphene synthesis on Rh(111). The temperature-programmed annealing and direct annealing growth pathways are designed to synthesize high-quality graphene.